2013
DOI: 10.1021/am404206v
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Detection Platform with Boronic-Acid-Containing Zwitterionic Polymer Brush

Abstract: Development of technologies for biomedical detection platform is critical to meet the global challenges of various disease diagnoses, especially for point-of-use applications. Because of its natural simplicity, effectiveness, and easy repeatability, random covalent-binding technique is widely adopted in antibody immobilization. However, its antigen-binding capacity is relatively low when compared to site-specific immobilization of antibody. Herein, we report that a detection platform modified with boronic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 65 publications
1
42
0
Order By: Relevance
“…The C1s XPS spectra could provide further information about the introduced functional groups on MIL‐100‐B. For a BBDC/BTC ratio of 1:4, the deconvoluted C1s peak (Figure d) consists of four peaks, which could be assigned to C in C‐B (283.9 eV), C‐C/C=C (284.6 eV), C‐O (285.7 eV), and O‐C=O (288.5 eV), respectively . Similar peaks could be observed in the deconvoluted C1s peak of MOFs with BBDC/BTC feed ratios of 1:2.3 (Figure e) and 1:1.5 (Figure f).…”
Section: Resultsmentioning
confidence: 56%
“…The C1s XPS spectra could provide further information about the introduced functional groups on MIL‐100‐B. For a BBDC/BTC ratio of 1:4, the deconvoluted C1s peak (Figure d) consists of four peaks, which could be assigned to C in C‐B (283.9 eV), C‐C/C=C (284.6 eV), C‐O (285.7 eV), and O‐C=O (288.5 eV), respectively . Similar peaks could be observed in the deconvoluted C1s peak of MOFs with BBDC/BTC feed ratios of 1:2.3 (Figure e) and 1:1.5 (Figure f).…”
Section: Resultsmentioning
confidence: 56%
“…1). [8][9][10][11][12][13][14][15][16][17][18] An overview of these articles is given in Table 1. 6 Oriented Ab immobilization using boronic acids (through the same reaction) was reported for the first time in 2009 by Lin et al, 7 and has appeared in another eleven papers since then.…”
Section: Introductionmentioning
confidence: 99%
“…The rearrangement of boronate esters in which the esters dissociate by hydrolysis to yield free boronic acids and diols is greatly affected by both pH as well as the presence of other competing saccharides [27]. For example, it has been shown that at alkaline pH values high levels of antibody dissociation are observed upon incubation with sugar-containing media [28]. In the case of immunosensors, the buffering systems usually employed are in the physiological pH range, while exposure to complex sample matrices is highly likely and depends on the application.…”
Section: Resultsmentioning
confidence: 99%